Many-criteria optimisation and decision analysis ontology and knowledge management - Basto-Fernandes, V.; Salvador, D.; Yevseyeva, I.; Emmerich, M. (Many-criteria optimization and decision analysis: State-of-the-art, present challenges, and future perspectives, 2023)
n this chapter, we present a Many-Criteria Optimisation and Decision Analysis (MACODA) Ontology and MACODA Knowledge Management Web-Based Platform (named MyCODA, available at http://macoda.club) for the research community. The purpose of this initiative is to allow for the collaborative development of an ontology to represent the MACODA knowledge domain and to make available a set of integrated tools for its use by researchers and practitioners. MyCODA is a knowledge-based platform to identify and describe MACODA research constructs, and to explore how these constructs relate to each other. It is designed to model and systematise the knowledge created by the MACODA research community, supporting features such as querying and reasoning, by means of formal logics, and use cases such as training new learners and finding research gaps in the MACODA research domain.